Perianal Crohn's Disease - Pogacnik, Javier Salgado; Salgado, Gervasio (Clinics in Colon and Rectal Surgery, 2019)
This article provides an overview of the principles in the evaluation and management of perianal Crohn's disease (CD). Manifestation-specific treatment is addressed including abscess, fistula, skin tags, hemorrhoids, fissure, ulcers, strictures, ano-, and rectovaginal fistulas as well CD-associated hidradenitis suppurativa.
Keywords: perianal; Crohn's disease; evaluation; management; abscess; fistula